Design, Characterisation and Evaluation of Sustained Release Formulation of Remogliflozin Etabonate - Aveek Datta,; Dr. Subhasis Maity,; Dr. Miltu Kr. Ghosh,; Dr. Kuntal Hazra, (Asian Journal of Pharmaceutical Research and Development, 2024)
Now-a-days Type 2 diabetes mellitus is a very crucial common disease and emerging condition that glucose level of Human body cannot be controlled. In case of Type-2 diabetes mellitus, pancreas does not produce enough insulin. In such a condition, we have to thing for a medicament for treating the disease; Remogliflozin Etabonate is such type of drug that efficacious and safe agent that we can administer in our body. The Half-Life of the drug is 120 minutes.This research has taken into consideration on improving the release pattern of the drug by sustaining its action at maximum level of time, using the different ratios of Polymer and discusses the individual studies performed during its development for design, characterization and evaluation of analytical and formulative profile, as well as in-vitro Characterization. In that case, this research work is hopefully very much useful for further proceeding and for large scale aspect in industrial point of view.